Perlindungan Konsumen Perpektif Keagamaan dalam Penggunaan Bahan Berbahaya pada Makanan - Imamul Hakim (Falah: Jurnal Ekonomi Syariah, 2016)
To fulfill of human need along with progress in science and engineering, appear various development in business, especially in food and beverage indutry. As efforts to meet the increase in needs, appear respons among supplier, with the various way, to meet various needs. In this context , done the addition of a chemical substance on the material food often known with food additive. But with progress, the hazardous materials that should not was suitable to consume added into food processing and drink. On the other hand, for a profit maximization, entrepreneurs didn’t see risk resulting from food products. The government had done various regulation to protect the consumer from the use of dangerous materials in food production. But the fact, the widespread a breach that occurs demanding a different approach to fix them. In order to alleviate this problem, the religion call a concept in different sides, spiritual element be important aspect to presented in the territories of material business to affect attitude the people of the activities daily life